Can you feel the body that you see? On the relationship between interoceptive accuracy and body image. (March 2017) - Zamariola, Giorgia; Cardini, Flavia; Mian, Emanuel; Serino, Andrea; Tsakiris, Manos
Highlights: Interoception and exteroception for body signals are linked. Lower interoceptive accuracy relates to difficulties in body image perception. People with lower interoceptive accuracy improve after a body perception task. Abstract: Interoception and exteroception for body signals are two different ways of perceiving the self: the first from within, the second from outside. We investigated the relationship between Interoceptive Accuracy (IAcc) and external perception of the body and we tested if seeing the body from an external perspective can affect IAcc. Fifty-two healthy female subjects performed a standard heartbeat perception task to assess the IAcc, before and after the Body Image Revealer (BIR), which is a body perception task designed to assess the different aspects of body-image. The performance of the lower IAcc group in the heartbeat perception task significantly improved after the exteroceptive task. These findings highlight the relations between interoceptive and exteroceptive body-representations, supporting the view that these two kinds of awareness are linked and interact with each other.